Integrating Organizational Support and Interactivity into the Technology Acceptance Model-A Study on Sustained User Engagement in E-Commerce Review Systems - Jia Xi-Hui; Wang Ying; Fei Teng; Luo Ting-Yun; Liu Hao-Ran; Jia Xian-Jin (中国科学与技术学报, 2025)
The surge in online shopping has resulted in an increased dependence on online product evaluations by consumers. However, the varying quality of reviews provided by businesses and consumers can introduce biased influences on consumer decision-making processes. To address this concern, Chinese online shopping platforms are introducing a "jury panel" mechanism to alleviate negative consumer experiences arising from inappropriate feedback. This research centers on the Meituan App case and utilizes an expanded Technology Acceptance Model (TAM) framework to explore concepts such as perceived ease of use, perceived usefulness, and usage intention within the framework of the assessment system. Furthermore, the study investigates external factors like perceived organizational support and perceived interactivity to comprehend their effects on system utilization. By analyzing how these elements impact perceived ease of use, perceived usefulness, and perceived playfulness, the research aims to construct a quantitative model that clarifies the factors influencing consumers’ ongoing intention to use the assessment system. Through this investigation, the study aims to enrich the TAM theory, unveil the internal mechanisms influencing consumer engagement in the assessment system, and provide recommendations for enhancing the system and formulating strategies to promote a healthy e-commerce environment.